The Precarious Center: Religious Leadership among African Christians - Kirsch, Thomas G. (Religion and society, 2014)
This article addresses a long-standing conundrum in the anthropology of religion concerning the ambiguous status of religious leaders: they are subjects of power in that they are able to exert power over others, yet they are objects of power in that they rely on empowerment through others. Taking African-initiated Pentecostal-charismatic Christianity in Zambia as my example, I argue that church leaders' strategies to stabilize their authority have unintended consequences since these strategies can contribute to the precariousness of their positions. By drawing fundamental distinctions between themselves and members of the laity as regards their own extraordinariness, church leaders raise high expectations about their own capacities that may turn out to be impossible to fulfill. Yet even the opposite strategy of strengthening one's authority by embedding oneself in socio-religious networks can eventually lead to a destabilization of church leaders' authority because it increases their dependence on factors that are beyond their control.